RNA sequencing of bipolar disorder lymphoblastoid cell lines implicates the neurotrophic factor HRP-3 in lithium's clinical efficacy. (3rd July 2019) - Milanesi, Elena; Voinsky, Irena; Hadar, Adva; Srouji, Ala; Maj, Carlo; Shekhtman, Tatyana; Gershovits, Michael; Gilad, Shlomit; Chillotti, Caterina; Squassina, Alessio; Potash, James B.; Schulze, Thomas G.; et al.
Abstract: Objectives: Lithium remains the oldest and most effective treatment for mood stabilisation in bipolar disorder (BD), even though at least half of patients are only partially responsive or do not respond. This study aimed to identify biomarkers associated with lithium response in BD, based on comparing RNA sequencing information derived from lymphoblastoid cell lines (LCLs) of lithium-responsive (LR) versus lithium non-responsive (LNR) BD patients, to assess gene expression variations that might bear on treatment outcome. Methods: RNA sequencing was carried out on 24 LCLs from female BD patients (12 LR and 12 LNR) followed by qPCR validation in two additional independent cohorts (41 and 17 BD patients, respectively). Results: Fifty-six genes showed nominal differential expression comparing LR and LNR (FC ≥ |1.3|, P  ≤ 0.01). The differential expression of HDGFRP3 and ID2 was validated by qPCR in the independent cohorts. Conclusions: We observed higher expression levels of HDGFRP3 and ID2 in BD patients who favourably respond to lithium. Both of these genes are involved in neurogenesis, and HDGFRP3 has been suggested to be a neurotrophic factor. Additional studies in larger BD cohorts are needed to confirm the potential of HDGFRP3 and ID2 expression levels in blood cells as tentative favourable lithium response biomarkers.